1976
DOI: 10.23986/afsci.71923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acidification of insecticide sprays in pest control of sugar beet seedlings

Abstract: The pH of dimethoate, formetanate and methidathion insecticide spray liquids was reduced from 8.0 to 4.0 by adding 0.1 M H3PO4. Acidification did not improve the effectiveness of sprays against Lygus rugulipennis, Chaetocnema concinna or Piesma maculatum. There were also no significant differences in root or top yields between plots treated with acidified insecticides and the incecticides alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This author also mentioned that C. concinna was one of the pests causing the most damage to rhubarb by eating holes or creating brown pits in the leaves. Varis (1976) studied the effect of acidification of insecticides in pest control of sugar beet seedlings. After field experiments, conducted between 1958 and 1973, Varis & Rautapaa (1976) concluded that dimethoate gave the highest increase in sugar beet root yields.…”
Section: Pest Statusmentioning
confidence: 99%
“…This author also mentioned that C. concinna was one of the pests causing the most damage to rhubarb by eating holes or creating brown pits in the leaves. Varis (1976) studied the effect of acidification of insecticides in pest control of sugar beet seedlings. After field experiments, conducted between 1958 and 1973, Varis & Rautapaa (1976) concluded that dimethoate gave the highest increase in sugar beet root yields.…”
Section: Pest Statusmentioning
confidence: 99%